Pavin Chachavalpongpun, Reinventing Thailand: Thaksin and his Foreign Policy, Singapur, Institute of Southeast Asian Studies, 2010, 354 pp. - Hernández, Rosángel (Estudios de Asia y África, 2014)
Pavin Chachavalpongpun, Reinventing Thailand: Thaksin and his Foreign Policy, Singapur, Institute of Southeast Asian Studies, 2010, 354 pp.